2001
DOI: 10.1152/ajpregu.2001.281.3.r1013
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability is reduced and IL-10 levels are increased in septic IL-6 knockout mice

Abstract: Sepsis is associated with increased intestinal permeability, but mediators and mechanisms are not fully understood. We examined the role of interleukin (IL)-6 and IL-10 in sepsis-induced increase in intestinal permeability. Intestinal permeability was measured in IL-6 knockout (IL-6 -/-) and wild-type (IL-6 +/+) mice 16 h after induction of sepsis by cecal ligation and puncture or sham operation. In other experiments, mice or intestinal segments incubated in Ussing chambers were treated with IL-6 or IL-10. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 50 publications
6
83
1
1
Order By: Relevance
“…We have reported that NPWDQ (aa 107-111 of s 2 -casein), which occurred in the EMC, inhibited OVA permeation in a Caco-2 cell model. 10) In this study, first we examined to determine whether NPWDQ would inhibit the permeation of FITC-dextran (a marker of paracellular transport 18) ) and HRP (that of transcellular transport 18) ) in vitro. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that NPWDQ (aa 107-111 of s 2 -casein), which occurred in the EMC, inhibited OVA permeation in a Caco-2 cell model. 10) In this study, first we examined to determine whether NPWDQ would inhibit the permeation of FITC-dextran (a marker of paracellular transport 18) ) and HRP (that of transcellular transport 18) ) in vitro. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro permeability was measured in Ussing chambers as described previously (15). Briefly, two jejunum segments per mouse were opened along the mesenteric border, rinsed, and pinned as intact sheets between siliconized Ussing half chambers.…”
Section: Methodsmentioning
confidence: 99%
“…31 In brief, mice were gavaged with 10 ml/kg of a solution of 22 mg/ml fluorescein isothiocyanate (FITC)-dextran (molecular mass 4 kDa, Sigma) in PBS, pH 7.4. Blood was collected from the inferior vena cava 3 hours after gavage, and plasma was collected by centrifugation at 3000 rpm for 20 minutes at 4°C.…”
Section: Intestinal Permeability Assaysmentioning
confidence: 99%